From Bama’s Karukku ([1992] 2014) to Yashica Dutt’s Coming Out as Dalit: A Memoir (2019): The Changing Nature of Dalit Feminist Consciousness - Bianca Cherechés (Revista Alicantina de Estudios Ingleses, 2023)
Dalit literature articulates the oppression and exploitation faced by Dalits in a caste-ridden society as it records their social and cultural lives before and after India’s independence. This cultural revolt that burgeoned in the 1970s has largely been Dalit male-centric in its orientation, adopting paternalistic and patronising tones towards Dalit women. As a consequence, Dalit women remained firmly encapsulated in the patriarchal roles of the silent, agenciless and ‘victimised sexual being,’ perpetuating thus gendered stereotypes. These accounts failed to properly address Dalit women’s predicament and the interlocking oppression of caste and gender, which compelled them to create a distinct space for themselves. Dalit women have traversed a long path over the last four decades. During this time, their consciousness has evolved in many ways as reflected in Dalit writing. Life narratives, such as Bama’s Karukku and Yashica Dutt’s Coming Out as Dalit: A Memoir, function as the locus of enunciation where agency and self-identity are attended and asserted by Dalit women, through different approaches. As the social location determines the perception of reality, this paper attempts a look at how these two texts tackle and bring to the centre the gendered nature of caste and the power relations that still affect Dalit women, from a heterogeneous standpoint. It further analyses how through form, language and subject matter, Dalit women attempt to defy generic conventions, depart from imposed identities, and build up resistance against this enduring double oppression and the forces that insist on homogenising Dalit body politics.